2019
DOI: 10.21203/rs.2.337/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical analysis of microbiologically proven fungal keratitis according to prior topical steroid use: A retrospective study in South Korea

Abstract: Background: To compare the clinical characteristics and treatment outcomes of microbiologically proven fungal keratitis between prior topical steroid users (PS) and no prior topical steroid users (NPS). Methods: Eighty-three cases with microbiologically proven fungal keratitis between January 2000 and December 2016 were reviewed retrospectively. Diagnosis of fungal keratitis was made through potassium hydroxide smear, culture, PCR, or biopsy. Baseline epidemiology, predisposing factors, clinical characteristi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This has also been observed by several other authors. [3][4][5][6][7][8] Majority of the patients belonged to the middle age group (21 to 60 years), possibly due to the same reason. History of trauma, especially with vegetative matter, maybe an essential risk factor for mycotic keratitis as shown by other authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has also been observed by several other authors. [3][4][5][6][7][8] Majority of the patients belonged to the middle age group (21 to 60 years), possibly due to the same reason. History of trauma, especially with vegetative matter, maybe an essential risk factor for mycotic keratitis as shown by other authors.…”
Section: Resultsmentioning
confidence: 99%
“…Indiscriminate use of steroids and antibiotics, use of contact lenses, immuno-compromised state and ocular surgery are other causes of increasing incidence of corneal infection. 3 Agricultural workers and laborers are the biggest occupational group as the highest incidence coinciding with the period of maximal activity. In India, a favorable tropical environment, coupled with a primarily agricultural population having a constant risk of plant exposure and low-income status are the predisposing factors for fungal infections.…”
mentioning
confidence: 99%
“…A recent retrospective chart review of fungal keratitis in a South Korean hospital found prior topical steroid use with worse disease progression, treatment failure, and more commonly necessitating surgical intervention. 14 Cessation of prior topical steroid use in misdiagnosed fungal keratitis presents with its own dilemma as it can further contribute to worsening inflammation and corneal necrosis. 4 Our case further emphasizes risks associated with topical steroid use in atypical cases of keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Voriconazole also has efficacy against yeasts. Corticosteroids have been shown to cause worse clinical outcomes and should be discontinued if a fungal cause is suspected [61].…”
Section: Therapy For Fungal Keratitismentioning
confidence: 99%